Strangers in a foreign land: the organizing of Catholic Latinos in the United States - Schultze, George E. (Lexington Books, 2007)
Aliens no more -- Catholicism and worklife -- U.S. labor history and Catholic participation -- World War I social reconstruction -- U.S. labor 1940s to 2000: Catholic labor schools, business unionism, the UFW -- A swing to the cultural left leaves the Catholic Church on the side lines -- A need for change